Analisis Daerah Rawan Kecelakaan Di Ruas Jalan Palangka Raya – Tangkiling - Devia Devia (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
The number of traffic accidents on roads from Palangka Raya to Tangkiling has increased. This is proved that it has increased every year. The road is functioned as the linking road among districts and it is also utilized as the main artery road. Accidents that are occurred in some parts of that road decrease the performance of the road. The aim of this study is to analyze the accident-prone area and its causes so that we are able to identify the handings of that area. This study aims to identify the blackspot points and variables that affect the accident rate (AR) as well as provide handlings for the accident-prone area. The statistic test was multiple linear regression tests using SPSS program. Based on the result of the analysis, it was found that the highest accident rate (AR) on the range of STA 3+000 to 4+000 on Tjilik Riwut road in Palangka Raya. Changes in land use, type of accident, gender, and high speed of vehicle make the accident rate increase. Therefore it is necessary to pay attention to the use of land beside the road so that the Road Benefit Space is free of all kinds of buildings